2019
DOI: 10.2196/12297
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Mobile Phone Apps for Lifestyle Modification in Diabetes: Systematic Review and Meta-Analysis

Abstract: BackgroundDiabetes and related complications are estimated to cost US $727 billion worldwide annually. Type 1 diabetes, type 2 diabetes, and gestational diabetes are three subtypes of diabetes that share the same behavioral risk factors. Efforts in lifestyle modification, such as daily physical activity and healthy diets, can reduce the risk of prediabetes, improve the health levels of people with diabetes, and prevent complications. Lifestyle modification is commonly performed in a face-to-face interaction, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
188
0
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(210 citation statements)
references
References 52 publications
(131 reference statements)
10
188
0
12
Order By: Relevance
“…Despite the growing number of studies using mobile technologies for diabetes management [ 10 , 11 , 15 ], the effectiveness of introducing apps to people with T2DM to support their self-management at large scale remains uncertain given the generally poor quality of apps [ 12 , 13 , 32 ], unmet consumer needs [ 14 ], and studies lacking robust designs with long-term evaluations [ 10 , 15 ]. The MDC program is highly innovative with its conversational element.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the growing number of studies using mobile technologies for diabetes management [ 10 , 11 , 15 ], the effectiveness of introducing apps to people with T2DM to support their self-management at large scale remains uncertain given the generally poor quality of apps [ 12 , 13 , 32 ], unmet consumer needs [ 14 ], and studies lacking robust designs with long-term evaluations [ 10 , 15 ]. The MDC program is highly innovative with its conversational element.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, people with diabetes expect apps to be engaging; incorporating multiple functions; and covering a broad range of content, including psychological and emotional support [ 14 ]. Although some recent systematic reviews and meta-analyses have indicated a modest effect for app-based interventions to support diabetes self-management [ 10 , 11 , 15 ], there still remains a great deal of uncertainty about their feasibility, acceptability, and effectiveness in the real world [ 10 , 15 - 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous mobile health research has focused more on self-management of chronic diseases than on prevention. In their systematic review and meta-analysis, Wu et al [ 34 ] investigated the effectiveness of mobile phone apps for diabetes self-management (including prediabetes, gestational diabetes, type 1 diabetes, and T2DM). They identified 3 studies that targeted prediabetes, 2 of which we also included in this review.…”
Section: Discussionmentioning
confidence: 99%
“…They identified 3 studies that targeted prediabetes, 2 of which we also included in this review. The overall conclusion of Wu et al [ 34 ] was that there was evidence for the effectiveness of app interventions in T2DM self-management, but not for prediabetes. Lunde et al [ 35 ] conducted a systematic review looking at various types of noncommunicable diseases and lifestyle advice.…”
Section: Discussionmentioning
confidence: 99%
“…Diverse Gesundheits-Apps zur Optimierung des Lebensstils können für die Prävention und Therapie genutzt werden [26][27][28][29]. Es gibt Gesundheits-Apps zum Selbstmanagement bei Gestationsdiabetes [27,30] oder Smartphone-Apps für Sportler mit Typ-1-Diabetes [31]. Ihre Qualität und ihr Nutzen sollten wissenschaftlich belegt sein und erst dann sollten sie allgemein empfohlen werden.…”
Section: Nutzen Und Nachteile Von Körperlicher Aktivität Bei Typ-1-diunclassified